Islamic Multiliteral Education: Study on Thinking of Imam Nawawi in Adabul Alim Wal Mutaalim - Hudzaifa Ahmad; Mahsun Jayadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
This article analyzes the concept of multiliterate Islamic education of Imam Nawawi in Adabul Alim Wal Muta'alim. This type of research is library research, namely research whose main object is books or other sources of literature. That is, data are sought and found through literature reviews from books that are relevant to the discussion. Imam Nawawi in the book Adabul Alim Wal Mutaalim has presented the concept of multiliter Islamic education with four relationships; that is, theocentric relations, linguistic relations, ethical relations, and juridical relations. At this point, the study of the thoughts of Imam Nawawi through the book Adabul Alim Wal Muta'allim as a strategic step to describe the concept of multiliter Islamic education that found its paradigmatic foothold. Keywords: Islamic education, Multiliteral Education, Imam Nawawi